Mobile Microscopy and Automated Image Analysis: The ease of cell counting and classification. Issue 1 (9th February 2018) - Pfeil, Juliane; Frohme, Marcus; Schulze, Katja
Abstract: Mobile microscopy and automated image analysis are powerful techniques for many applications. A mobile system that consists of a smartphone, an optical attachment and automated image recognition software in a cloud laboratory and its current and possible future applications are described in this article. The idea is to create a very fast, cheap, location‐ and knowledge‐independent system for many use cases.